Algorithms as figures: Towards a post-digital ethnography of algorithmic contexts. (April 2022) - Cellard, Loup
This article intervenes in contemporary discussions of critical algorithm studies about the meaning of the notion 'algorithm'. While many critical scholars as well as most public and private organisations understand this concept as a computational procedure instantiated by a programming code in a software stack, I argue that the algorithm is better understood as a 'figure'; a discursive short-hand pointing to diverse modes of procedural governance and not always digital ones. Since algorithmic figures are generated by a bundle of heterogeneous contexts, their emergence leads to conflicting visions about the reality, materiality and effects of algorithmisation. This article provides four ethnographic strategies to describe the contexts of production and circulation of algorithmic figures: observing the observers of algorithms; mapping and creating algorithmic figures; drawing relations across contexts of figuring; and analysing the transformative effects of algorithmic figures on the attempts to govern them.